ANALISIS TARAF HIDUP PETANI SKALA KECIL DI SUMATERA SELATAN - Imam Asngari (Department of Development Economics, Universitas Sriwijaya, 2011)
This study aims to assess the standard of living and the factors that affected on the livelihoods of small-scale farmers in South Sumatera. This study covers the factors that affect the living standards of the poor and not poor small scale farmers as the extent of land, productivity, creation of value added, efficiency, and aquaculture farming. Study site purposively determined, namely rice farmers in the district of OKU Timur and palm oil farmers in the district of Muara Enim. Farmers were randomly drawn sample strata based on land area and production. Data taken with a questionnaire and direct interviews with farmers. Total number of samples is 80 farmers. Methods of analysis, starting with the measure of productivity, calculated using the income approach to value-added, and the measure of efficiency. Verification of data on poverty using the poverty line for rural areas in 2010 BPS. The results showed that farmers with poor living conditions caused by low productivity, efficiency is also low, so that its income is low, less intensive farming and there has been stagnation and polarization of the land thus increasing the number of landless peasants. Poverty is also arising from the exploitation by the farmers themselves (self-exploitation) and the exploitation of market institutions are generally structured monopsony. While aspects of the cultivation of less intensive farming. Instead of small-scale farmers are not poor to better their living standards as productive, efficient, and the cultivation of more intensive farming. Keywords: standard of living, land, productivity, income, efficiency of, and intensification